Gonadotropins treatment prior to microdissection testicular sperm extraction in non-obstructive azoospermia: a single-center cohort study - Tianwen Peng; Chen Liao; Xin Ye; Zhicong Chen; Yu Lan; Xin Fu; Geng An (BMC, 2022)
Abstract Background Microdissection testicular sperm extraction (micro-TESE) in combination with ICSI can make paternity possible for non-obstructive azoospermia (NOA) patients. Testicular sperm can be successfully retrieved in nearly half of NOA patients. Nevertheless, not many convincing protocols are established to improve sperm retrieval rate (SRR). The goal of this study was to evaluate whether gonadotropins therapy before micro-TESE could improve sperm retrieval rate and affect the ICSI outcomes in non-obstructive azoospermia patients with hypergonadotropic hypogonadism. Methods This retrospective cohort study included a total of 569 non-obstructive azoospermia men who underwent micro-TESE with or without 3-month of preoperative hCG / hCG plus highly purified urinary FSH (uFSH) between January 2016 and December 2019. The primary outcome was the sperm retrieval rate of micro-TESE. Results Sperm was found in 27 patients among 395 NOA men who accepted preoperative gonadotropins treatment (6.8%, 27/395) in post-treatment semen analysis for ICSI. One hundred forty nine out of 542 patients could successfully obtain enough sperm for ICSI through the micro-TESE (overall SRR = 27.5%). There was a statistically significant difference in the SRR between the preoperative gonadotropins treatment and non-gonadotropins treatment groups (31.2%, 115/368 vs. 19.5%, 34/174, P = 0.006). In the multivariable analysis with IPTW according to the propensity score, there was a significant association between preoperative gonadotropins treatment and the SRR (OR, 1.59; 95% CI: 1.02-2.52; P = 0.042). No differences in the clinical pregnancy rate, live birth delivery rate, or miscarriage rate were observed between the two groups. Conclusion Preoperative gonadotropins therapy seems to have a role in improving SRR in NOA patients with hypergonadotropic hypogonadism. We found that gonadotropins therapy had no effect on ICSI clinical outcomes and live birth.